Bifurcations of Nonconstant Solutions of the Ginzburg-Landau Equation - Norimichi Hirano; Sławomir Rybicki (Abstract and Applied Analysis)
We study local and global bifurcations of nonconstant solutions of the Ginzburg-Landau equation from the families of constant ones. As the topological tools we use the equivariant Conley index and the degree for equivariant gradient maps.